A network analysis to identify mediators of germline-driven differences in breast cancer prognosis - Escala-Garcia, Maria; Arndt, Volker; Brenner, Hermann; Chang-Claude, Jenny; Kaaks, Rudolf; Burwinkel, Barbara; Canzian, Federico; Hamann, Ute; Sohn, Christof (Nature Communications, 2020)
In breast cancer the contribution of different genetic variants to disease heritability is complex and not fully understood. Here, the authors present a network-based analysis in 84,567 patients studying ~7.3 million variants, identifying gene modules associated with breast cancer survival.
Gesehen am 07.04.2020